Why Does Income Inequality Persist? Examining The Roles Of Poverty, Unemployment, Zakat, And Regional Government Expenditure In Three Indonesian Provinces - Kharisma Rindang Sejati (IQTISHADUNA: Jurnal Ekonomi dan Keuangan Islam, 2026)
Income inequality remains one of the major obstacles to regional economic development in Indonesia. Various redistributive instruments, including regional government expenditure and zakat distribution, have been continuously expanded; however, income inequality persists. This study aims to examine the effects of poverty, unemployment, the ratio of zakat distribution to Gross Regional Domestic Product (GRDP), and regional government expenditure on income inequality in three Indonesian provinces, namely West Java, West Sumatra, and South Kalimantan, during the period 2020–2024. These provinces were purposively selected due to their distinct economic, social, and zakat management characteristics, which provide variation in income inequality levels. The study employs semester-based panel data consisting of 30 observations. Model selection was conducted using the Chow test, which indicated that the Fixed Effect Model was more appropriate than the Common Effect Model. The results reveal that poverty has a positive and significant effect on income inequality, with a coefficient of 0.019383. Unemployment, on the other hand, has a negative and statistically significant effect, with a coefficient of -0.008109 and a p-value of 0.0371. In contrast, the ratio of zakat distribution to GRDP and regional government expenditure do not have a significant effect on income inequality. These findings suggest that income inequality in the three provinces is driven more by structural factors than by the redistributive instruments examined in this study. Keywords: Income Inequality, Poverty, Unemployment, Zakat, Regional Government Expenditure, Panel Data,